Inter-individual variability of neurotransmitter receptor and transporter density in the human brain - Hansen, Justine Y.; Tuisku, Jouni; Johansson, Jarkko; Chang, Zeyu; McGinnity, Colm J.; Beliveau, Vincent; Guimond, Synthia; Ganz, Melanie; Nørgaard, Martin; Galovic, Marian; Bezgin, Gleb; Cox, Sylvia M. L.; et al. (Springer Nature, 2026)
Neurotransmitter receptors guide the propagation of signals between brain regions. Mapping receptor distributions in the brain is therefore necessary for understanding how neurotransmitter systems mediate the link between brain structure and function. Normative receptor density can be estimated using group averages from Positron Emission Tomography (PET) imaging. However, the generalizability and reliability of group-average receptor maps depends on the inter-individual variability of receptor density, which is currently unknown. Here we collect group standard deviation brain maps of PET-estimated protein abundance for 12 different neurotransmitter receptors and transporters across 7 neurotransmitter systems, including dopamine, serotonin, acetylcholine, glutamate, GABA, cannabinoid, and opioid. We illustrate how cortical and subcortical inter-individual variability of receptor and transporter density varies across brain regions and across neurotransmitter systems. We complement inter-individual variability with inter-regional variability, and show that receptors that vary more across brain regions than across individuals also demonstrate greater out-of-sample spatial consistency. Altogether, this work quantifies how receptor systems vary in healthy individuals, and provides a means of assessing the generalizability of PET-derived receptor density quantification.